Monetary policy press releases of 24 inflation targeting central banks: A comparison of their key features and complexity - Piotr Szczerba; Anna Wojtyniak; Joanna Niedźwiedzińska; Wojciech Bogdanowicz (Journal of Central Banking Theory and Practice, 2024)
This paper describes the process of constructing a dataset of available online press releases related to monetary policy decisions published by central banks that have been pursuing a form of inflation targeting. A total of 3,807 documents were considered, as the review encompasses 24 central banks over the past 30 years. To prepare the dataset for text-mining analysis, a cleaning procedure has been performed, which is also presented in detail. The next step was to look at the readability of the documents in order to detect any patterns in its changes. We find that while there is a significant variation between central banks, there is no clear time trend in the readability of the monetary policy press releases, i.e. some central banks tend to have easier-to-read press releases than others, and this does not change with time. In turn, there is a weak indication that following the Global Financial Crisis outbreak and the European Sovereign Debt Crisis apogee, as well as at the time of withdrawing unconventional measures introduced in response to those two emergencies, press releases of advanced economy inflation targeters got temporarily harder-to-read. Overall, this paper can be viewed as a first attempt towards assessing qualitatively central banks' transparency, with respect to a flagship communication tool of inflation targeters, namely their monetary policy press releases.
Keywords: E52; E55; 330; Central bank communication; Press releases; Text mining